Reply to: Letter to the Editor regarding "Covid-19 transmission in fitness centers in Norway—a randomized trial" - Lise M. Helsingen; Magnus Løberg; Michael Bretthauer; Mette Kalager (BMC Public Health, 2022)
Abstract In this correspondence we respond to critique of our randomized trial of Covid-19 transmission in fitness centers. The trial was performed in Norway during May and June 2020.